2002
DOI: 10.1128/jcm.40.4.1326-1332.2002
|View full text |Cite
|
Sign up to set email alerts
|

Detection by Reverse Transcription-PCR and Genetic Characterization of Field Isolates of Swine Hepatitis E Virus from Pigs in Different Geographic Regions of the United States

Abstract: Hepatitis E virus (HEV) is an important public health concern in many developing countries. HEV is also endemic in some industrialized counties, including the United States. With our recent discovery of swine HEV in pigs that is genetically closely related to human HEV, hepatitis E is now considered a zoonotic disease. Human strains of HEV are genetically heterogenic. So far in the United States, only one strain of swine HEV has been identified and characterized from a pig. To determine the extent of genetic v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
294
3
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 339 publications
(311 citation statements)
references
References 41 publications
11
294
3
3
Order By: Relevance
“…Seroprevalence studies indicated that about 15-70% of pigs were infected with HEV in several countries [3,4,12,25]. The infection rate of pigs measured by detecting HEV RNA in the fecal specimens showed approximately 40% of pigs in the U.S.A. were infected by HEV [7]. A few studies were conducted in Korea to determine HEV infection rates with swine sera or liver tissues [4,8].…”
mentioning
confidence: 99%
“…Seroprevalence studies indicated that about 15-70% of pigs were infected with HEV in several countries [3,4,12,25]. The infection rate of pigs measured by detecting HEV RNA in the fecal specimens showed approximately 40% of pigs in the U.S.A. were infected by HEV [7]. A few studies were conducted in Korea to determine HEV infection rates with swine sera or liver tissues [4,8].…”
mentioning
confidence: 99%
“…5 In the USA 25 (26.3%) 2-to 4-month-old pigs out of 95 were reported to be shedding the virus. 7 It takes between 2 and 3 weeks from initial infection to the time when HEV is excreted in feces, 11 and the viral shedding can last up to 7 weeks. Considering the fact that the maximum prevalence recorded in this work was found in the first month of feeding (around 13 to 16 weeks of age), it is reasonable to extrapolate that the majority of animals were infected at 3 to 6 weeks of age from contact with the sows.…”
mentioning
confidence: 99%
“…Two pairs of degenerated oligonucleotide primers were used to amplify a 348-basepair (bp) fragment of open reading frame 2 (ORF-2) of HEV using an RT-nested PCR. 7 These primers were based on 18 human HEV sequences and the swine HEV prototype strain from USA. A positive control from a naturally infected pig (GenBank accesion number AY323506) was included in each procedure.…”
mentioning
confidence: 99%
“…Pigs are supposed to be infected with HEV via the fecal-oral route continuously, since pigs habitually eat feces naturally. Several epidemiological studies reported HEV shedding in up to 17-week-old pigs [23,[30][31][32]. An opportunity to come in contact with contaminated feces increases the intake of virus by pigs.…”
Section: Discussionmentioning
confidence: 99%